PENGEMBANGAN APLIKASI PEMBELAJARAN MY SOLAR SYSTEM PADA MATERI BUMI DAN TATA SURYA - Fatmawati, Sulis; Hadi, Wiwin Puspita; Sidik, Rahmad Fajar; Wahyuni, Eva Ari; Wulandari, Ana Yuniasti Retno (Natural Science Education Research, 2025)
This study aims to determine the feasibility, response, media readability, and students' understanding of Nature of Science. This type of research is a pure development with the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate). The research was conducted at Kanzul Ulum Junior High School grade VII with a total of 27 students for the 2023-2024 school year. The research instrument used a validation questionnaire of media experts, material experts, responses, readability, and Nature of Science comprehension tests. Based on the research, conclusions were obtained: (1) The results of material feasibility and media feasibility obtained a score of 1 with very valid criteria (2) The results of students' responses in individual trials 86.71%, small group trials 84.37% with very good criteria. Meanwhile, the large group test 77.83% with good criteria (3) The results of media readability in the individual trial 87.29%, the small group trial 85.88% with very good criteria.